2021
DOI: 10.48550/arxiv.2112.11354
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classically-inspired Mixers for QAOA Beat Goemans-Williamson's Max-Cut at Low Circuit Depths

Abstract: We generalize the Quantum Approximate Optimization Algorithm (QAOA) of Farhi et al. (2014) to allow for arbitrary separable initial states and corresponding mixers such that the starting state is the most excited state of the mixing Hamiltonian. We demonstrate this version of QAOA by simulating Max-Cut on weighted graphs. We initialize the starting state as a warm-start inspired by classical rank-2 and rank-3 approximations obtained using Burer-Monteiro's heuristics, and choose a corresponding custom mixer. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…[93] which also found that faster error correcting codes are needed to make heuristics for combinatorial optimization competitive. This also suggests that warm-starting methods [94][95][96] will be required to get a quantum advantage in combinatorial optimization with heuristic algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…[93] which also found that faster error correcting codes are needed to make heuristics for combinatorial optimization competitive. This also suggests that warm-starting methods [94][95][96] will be required to get a quantum advantage in combinatorial optimization with heuristic algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…[97] which also found that faster error correcting codes are needed to make heuristics for combinatorial optimization competitive. This also suggests that algorithmic improvements to QAOA [95,98] such as warm-start methods [99][100][101] will be required to get a quantum advantage in combinatorial optimization with heuristic algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of other approaches have been studied in Refs. [26,[28][29][30]. We hope that these works will stimulate more effort in combining the strengths of the two computing paradigms to advance the state of the art for combinatorial optimization.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, this has been rarely done in previous works (except that classical techniques for continuous optimization have been used to tune the parameters in the ansatz circuits). A few exceptions are the recent works on warm-starting quantum optimization [26,[28][29][30]. In particular, Egger et al [26] proposed the warmstarted QAOA (WS-QAOA) in which the initial state and mixing operator are constructed based on the continuous solution of the Quadratic Programming (QP) or Semidefinite Programming (SDP) relaxation of the original problem, and showed that this algorithm outperforms standard QAOA at low depths.…”
Section: Introductionmentioning
confidence: 99%